Examining the mediating role of employee creativity: a study of how knowledge management influences and employee performance works in higher education institutions - Megha Ojha; Vinay Kandpal; Archana Singh (Future Business Journal)
Abstract Higher education institutions (HEIs) endeavor to increase employee performance (EP) by fostering employee creativity (EC) and knowledge management (KM) in order to gain and maintain a competitive edge. While taking into account the user's viewpoint on the impact of knowledge management (KM) processes—more especially, knowledge creation, retention, dissemination, and utilization—in HEIs, this study critically reviews the body of current literature. The study primarily examines how creative motivation may improve productivity among employees and how employee creativity can act as a mediator in the interaction between knowledge management and employee performance. A structured survey was administered to 432 academic staff members from India's research-intensive HEIs, and SPSS and AMOS were used for statistical analysis. The results show that employee performance is significantly impacted by knowledge management both directly and indirectly through employee inventiveness. In order to maximize knowledge-driven innovation and productivity, academic administrators and policymakers can benefit greatly from the insights, this study provides on the dynamic interactions among knowledge management, employee creativity, and institutional performance in HEIs.